(untitled) (Heritage, 2022)
Taking into consideration that the geographical distribution of the specific wedding terms related to wedding customs and rituals in Serbian ethnic and dialectal regions is still rather unknown, as well as the fact that the ethnological monographic studies contain relatively detailed descriptions of the practices and the “standardized” forms used in naming, this paper presents the inventory of the terms used in naming people who take part in the wedding customs and rituals, based on the ethnic-dialectal materials collected in and around Leposavić, with the aim of placing the linguistic and ethnographic elements in the cultural and areal context.